The Allegiance of White American Evangelicals to Donald Trump - Bieber, Kenneth (Exchange, 2020)
This article discusses why American evangelical Christians, particularly white evangelicals, have granted overwhelming support to Donald Trump, first as a presidential candidate in 2016, and then as president since his inauguration in January 2017. The loyalty afforded to him by this voting bloc results in an abandonment of the values and priorities of the greater Christian mission, exchanging faithful discipleship for political expediency. While this demographic of voters does not explicitly renounce the Christian faith or their belief in the authority of Scripture, the concerns exhibited in their fidelity to President Trump as a monarchical figure stand in contrast to both biblically-based evangelicalism and historic American political values.